2019
DOI: 10.1001/jamadermatol.2019.0434
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Views About Skin Self-examination After Treatment for Localized Melanoma

Abstract: IMPORTANCE Skin self-examination (SSE) is a key factor in the early detection of melanoma, and many new and recurrent melanomas are first detected by patients themselves or their family members. OBJECTIVE To explore the views of patients with melanoma regarding SSE in general, as well as their attitudes toward using novel digital technologies to support their own SSE. DESIGN, SETTING, AND PARTICIPANTS Qualitative study with semistructured interviews that were conducted from June 20 to December 12, 2016, with 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Contextualizing our results within the medical literature is limited by the paucity of data on how patients perceive AI for skin cancer screening. Dieng et al 16 found that patients lack confidence in their ability to undertake skin self-examination after treatment for localized melanoma and that some patients are receptive to assistance from new digital technologies. In line with the symbiosis theme in our study, Tran et al 17 found that most patients were ready to accept the use of AI for skin cancer screening after reading a vignette but only under human control.…”
Section: Discussionmentioning
confidence: 99%
“…Contextualizing our results within the medical literature is limited by the paucity of data on how patients perceive AI for skin cancer screening. Dieng et al 16 found that patients lack confidence in their ability to undertake skin self-examination after treatment for localized melanoma and that some patients are receptive to assistance from new digital technologies. In line with the symbiosis theme in our study, Tran et al 17 found that most patients were ready to accept the use of AI for skin cancer screening after reading a vignette but only under human control.…”
Section: Discussionmentioning
confidence: 99%
“…Other qualitative analysis among melanoma patients also found a lack of confidence to perform SSE and a preferred reliance on skin checks by health professionals. 46 This is of concern when studies show that self-efficacy is a key facilitator of SSE. 43,44 Low self-efficacy may be due to the complexity of the task to be performed, which highlights the need for an easy and clear tool.…”
Section: Discussionmentioning
confidence: 99%
“…Any AI system intended as a prevention tool to support lay people in self-screening could represent a significant step towards fostering patients' active involvement in prevention efforts, especially given the shift towards telemedicine since the beginning of the COVID-19 pandemic. Research also suggests that patients are open to using new digital solutions for performing skin selfexaminations, as long as they receive adequate technical support for using these tools (Dieng et al, 2019) and don't feel that they compromise the doctor-patient relationship (Nelson et al, 2020). However, there are also certain challenges to the introduction of these new tools from the patient's point of view.…”
Section: The Patient Viewmentioning
confidence: 99%